Design, fabrication and characterization of a microactuator for nebulization of fluids - Yasenov, Nedyu Nedev; Berberich, S. E.; Frey, Lothar; Ryssel, Heiner (2004)
This article deals with basic investigations of the development and manufacturing process of a piezoelectric driven microactuator for nebulization of fluids. The concept of the fabrication of the micronebulizer will be introduced. First fundamental investigations on materials characterization and process technology for the electrodes and piezoelectric A1N layers will be presented. A1N thin films have been depositetd by reactive sputtering technique and have been characterized with dielectric and ferroelectric measurements.